Extreme wildfire events and disasters : root causes and new management strategies - Tedim, Fantina; Leone, Vittorio; McGee, Tara K., 1965- (Elsevier, 2020)
Extreme Wildfire Events and Disasters: Root Causes and New Management Strategies highlights the urgent need for new methods to prepare and mitigate the effects of these events. Using a multidisciplinary, socio-ecological approach, the book discusses the roots of the problem, presenting a new, innovative approach to wildfire mitigation based on the operational concept of Fire Smart Territory (FST). Under the guidance of its expert editors, the book highlights new ways to prevent and respond to extreme wildfire events and disasters through sustainable development, thus revealing better management methods and increasing protection of both the natural environment and the vulnerable communities within it. Key Features: Reveals the complexity of extreme wildfire events and disasters in an accessible, comprehensive and multidisciplinary way; Reviews the ground-breaking concept of Fire Smart Territory (FST) which offers an opportunity to reduce wildfire occurrence and severity through measures that promote sustainable development; Proposes a new perspective on disaster risk reduction to help researchers, planners and professionals successfully adapt their methods for mitigating current and future issues. --